Effect of material thickness on Duration, hole characteristics, and drilling mechanism on micro-laser drilling - Haneef, Mohd Sabki (2023)
Recent advancement in manufacturing technology has led to the development of miniature products in the fields of automobiles, aerospace and robotics. This process involves high power intensity from the laser to break down the bond between molecules of the workpiece, hence forming a hole in the workpiece. However, as the material thickness increases, ablating away the material becomes more difficult and can affect the hole characteristics and the duration itself. This project aims to study the effect of material thickness on the laser duration and hole geometry of micro-drilled holes. This research also aims to analyse the mechanism of the hole formation during laser micro-drilling. The material used in this research is SS304 sheet metal with three different thicknesses, 100μm, 200μm and 300μm respectively. Besides, laser marking machine, Herolaser ML- MF-A01 IPG with 30-Watt fiber laser was used. The result showed that the size of the hole diameter for each material thickness is slightly constant for the top surface but has a decreasing value at the bottom surface which in range of 140.71μm-124.05μm. Meanwhile, the duration that needed to drill the hole for all the material thicknesses was in between 0.017s to 0.292s. In addition, the other characteristics such as hole taper, material redeposition and surface roughness have an influence on the differences in material thickness. The hole formation mechanism is generally divided into two phases, which is the drilling that has yet to be a ‘through-hole’ and the next phase is when the hole has been drilled until the bottom surface. Overall, this thesis demonstrates that laser micro-drilling may be a potential alternative to existing micro-drilling methods because duration and hole characteristics can still be considered. Furthermore, analysing the formation of the micro- hole may provide a better comprehension of this process.